The Effect of Organizational Culture on Performance of Government Internal Supervisory Apparatus (APIP) in The National Indonesian Navy - Soetjahjo Niti Tisno Harijono; Billy Tunas; Hamidah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2019)
Every Government Internal Supervisory Apparatus aims to improve performance through organizational Culture. The purpose of this study is analyzing the influence of organizational culture on the performance of government internal supervisors in the National Indonesian Navy. This research use quantitative study by using the Path Analysis method with a sample of 96 Government Internal Supervisors. The results of the study show that there is a direct influence of organizational culture on performance. Thus, the national Indonesian navy should put more attention regarding the Organizational Culture including discipline, efficiency, ethics, scope of work, work orientation and work implementation instructions.